Family functioning and mobile phone addiction in university students: Mediating effect of loneliness and moderating effect of capacity to be alone - Li, Guan-Ru; Sun, Jian; Ye, Jia-Nuo; Hou, Xiao-Hui; Xiang, Ming-Qiang (Frontiers in Psychology, 2023)
Background With the increasing popularity of smartphones, mobile phone addiction in university students has attracted widespread societal attention. Previous studies showed that family functioning and mobile phone addiction are related. However, the potential mechanisms involved in this relationship are unknown. This study examined the mediating effect of loneliness and the moderating effect of capacity to be alone on the relationship between family functioning and mobile phone addiction. Methods A total of 1,580 university students were recruited. A cross-sectional study design and online questionnaire survey were employed to measure demographic variables, family functioning, loneliness, capacity to be alone, and mobile phone addiction in university students. Results Family functioning is a significantly negative predictor of mobile phone addiction in university students, and loneliness has a mediating effect on the relationship between family functioning and mobile phone addiction. The capacity to be alone has moderating effects on the relationship between family functioning and loneliness and between family functioning and mobile phone addiction, and these correlation is stronger in university students with a low capacity to be alone. Conclusion The moderated mediation model in this study improves understanding of the correlation between family functioning and mobile phone addiction in university students. Education professionals and parents should pay particular attention to family functioning in mobile phone addiction, particularly university students with low capacity to be alone.